Clinical Significance of Incidental Rolandic Spikes in Children With Absence Epilepsy. (October 2019) - Datta, Anita N.; Wallbank, Laura; Mak, Jeremy C. H.; Wong, Peter K. H.
Purpose: Absence epilepsy and benign epilepsy of childhood with central temporal spikes are common childhood epilepsy syndromes. Although 3-Hz generalized spike-wave discharges are almost always associated with absence seizures, rolandic spikes can be present in individuals without rolandic seizures. The co-occurrence of 3-Hz generalized spike-wave and rolandic spikes is very rare. Our objective was to compare clinical features of patients with absence epilepsy with and without rolandic spikes, to determine if the additional feature of rolandic spikes has any clinical significance. Methods: Clinical information of 17 children with absence epilepsy and rolandic spikes was compared to an age-matched control group of 90 children with absence epilepsy. Results: Although most patients had excellent seizure control at follow-up, epilepsy comorbidities (cognitive and emotional problems) were observed. Comparing study vs control groups, there was no difference with anxiety (2 [11.8%] vs 8 [9%]), behavioral issues (4 [23.5%] vs 10 [11%]), mood disorders (0 vs 2 [2%]), and attention-deficit hyperactivity disorder (4 [24%] vs 10 [11%]). Significant differences were also observed: more global-developmental (5 [29%] vs 5 [6%], P < .009) and expressive-language (4 [24%] vs 5 [6%], P < .034) delay and more difficulties with school performance (11 [65%] vs 32 [36%], P < .025), especially with language-related tasks (6 [35%] vs 5 [6%], P < .001). Conclusion: Our results confirm the presence of additional epilepsy comorbidities in patients with absence epilepsy when rolandic spikes are present. Rolandic spikes in patients with absence epilepsy may be a marker of additional cognitive challenges that physicians should be aware of.